Alcoholics Anonymous and 12-Step Facilitation Treatments for Alcohol Use Disorder: A Distillation of a 2020 Cochrane Review for Clinicians and Policy Makers. (6th July 2020) - Kelly, John F; Abry, Alexandra; Ferri, Marica; Humphreys, Keith
ABSTRACT: Aims: A recently completed Cochrane review assessed the effectiveness and cost-benefits of Alcoholics Anonymous (AA) and clinically delivered 12-Step Facilitation (TSF) interventions for alcohol use disorder (AUD). This paper summarizes key findings and discusses implications for practice and policy. Methods: Cochrane review methods were followed. Searches were conducted across all major databases (e.g. Cochrane Drugs and Alcohol Group Specialized Register, PubMed, Embase, PsycINFO and ClinicalTrials.gov) from inception to 2 August 2019 and included non-English language studies. Randomized controlled trials (RCTs) and quasi-experiments that compared AA/TSF with other interventions, such as motivational enhancement therapy (MET) or cognitive behavioral therapy (CBT), TSF treatment variants or no treatment, were included. Healthcare cost offset studies were also included. Studies were categorized by design (RCT/quasi-experimental; nonrandomized; economic), degree of manualization (all interventions manualized versus some/none) and comparison intervention type (i.e. whether AA/TSF was compared to an intervention with a different theoretical orientation or an AA/TSF intervention that varied in style or intensity). Random-effects meta-analyses were used to pool effects where possible using standard mean differences (SMD) for continuous outcomes (e.g. percent days abstinent (PDA)) and the relative risk ratios (RRs) for dichotomous. Results: A total of 27 studies (21 RCTs/quasi-experiments, 5 nonrandomized and 1 purely economic study) containing 10, 565 participants were included. AA/TSF interventions performed at least as well as established active comparison treatments (e.g. CBT) on all outcomes except for abstinence where it often outperformed other treatments. AA/TSF also demonstrated higher health care cost savings than other AUD treatments. Conclusions: AA/TSF interventions produce similar benefits to other treatments on all drinking-related outcomes except for continuous abstinence and remission, where AA/TSF is superior. AA/TSF also reduces healthcare costs. Clinically implementing one of these proven manualized AA/TSF interventions is likely to enhance outcomes for individuals with AUD while producing health economic benefits. Abstract : Data bases up till August 2019 were searched for randomized controlled and other studies in participants with alcohol use disorders that compared the efficacy and costs of treatment that facilitated use of AA versus treatment using other methods such as cognitive behavior therapy and motivational enhancement therapy. The search revealed 27 studies pertaining to 10, 565 persons. Meta-analyses showed that AA and facilitating use of AA ('TSF') produced similar benefits to other treatments on all drinking-related outcomes except for continuous abstinence and remission, where AA/TSF was superior. Studies analyzing costing found that use of AA/TSF also tended to reduce healthcare costs.